The leaves of the seasoning plant Litsea cubeba inhibit the NLRP3 inflammasome and ameliorate dextran sulfate sodium-induced colitis in mice - Wong, Wei-Ting; Wu, Chun-Hsien; Li, Lan-Hui; Hung, De-Yu; Chiu, Hsiao-Wen; Hsu, Hsien-Ta; Ho, Chen-Lung; Chernikov, Oleg V.; Cheng, Shu-Meng; Yang, Shih-Ping; Chung, Chih-Hsin; Hua, Kuo-Feng; et al. (Frontiers in Nutrition, 2022)
The intracellular sensor NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome controls caspase-1 activity and the maturation and release of the cytokines interleukin (IL)-1β and IL-18. The NLRP3 inflammasome has attracted the attention of the pharmaceutical industry because it promotes the pathogenesis of many diseases, making it a promising target for drug development. Litsea cubeba (Lour.) is a plant traditionally used as a seasoning in Taiwan and in other Asian countries. In this study, we investigated the inhibitory activity of the leaves of L. cubeba against the NLRP3 inflammasome. We found that the ethanol extract of L. cubeba leaves (MLE) inhibited the NLRP3 inflammasome in macrophages by reducing caspase-1 activation and IL-1β secretion. MLE reduced pyroptosis in macrophages and inhibited the release of NLRP3 and apoptosis-associated speck-like protein containing a CARD (ASC). In a mechanistic study, MLE reduced mitochondrial reactive oxygen species production and preserved mitochondrial integrity, which led to reduced mitochondrial DNA release into the cytosol. MLE did not reduce the expression levels of NLRP3, IL-1β precursor or TNF-α in lipopolysaccharide (LPS)-activated macrophages. These results indicated that MLE inhibited the NLRP3 inflammasome by suppressing the activation signals of the NLRP3 inflammasome but not by reducing the priming signal induced by LPS. In addition, oral administration of MLE (20-80 mg/kg) ameliorated dextran sulfate sodium-induced colitis in a mouse model. Notably, mice that received MLE (1 and 2 g/kg) daily for 7 days did not exhibit visible side effects. Gas chromatography-mass spectrometry analysis found that α-Terpinyl acetate (27.2%) and 1,8-Cineole (17.7%) were the major compounds in MLE. These results indicated that L. cubeba leaves have the potential to be a nutraceutical for preventing and improving NLRP3 inflammasome-related diseases.